Evaluation of sustainable development considering natural conditions: A parametric slacks-based measure of efficiency approach. (15th March 2022) - Wen, Xiaojie; Yao, Shunbo; Sauer, Johannes
Abstract: In 2019, the Chinese government proposed a national strategy to promote high-quality, sustainable development in the Yellow River Basin, an ecologically fragile and economically less-developed region in China. Regarding this national strategy, the unresolved question is how to zone the research area scientifically and improve the performance of local governments accordingly. With this issue in mind, we assess the level of sustainability across counties in the Yellow River Basin from 2005 to 2015 and explore the zoning strategies on the basis of economic and environmental performance through a slacks-based measure of efficiency approach (SBM). Meanwhile, under the consideration of natural endowment, a three-stage parametric slacks-based measure of efficiency approach (parametric SBM) is employed to objectively evaluate the sustainable performance of local governments. Results reveal that: i) natural conditions could be catalysts for sustainable development in some counties but could also be inhibitors in other counties; ii) on average, around 35% of counties have lower sustainable efficiencies after removing the influence of natural conditions; iii) the trade-off relationship between environment and economy could be confirmed, which helps us to initially construct the zoning strategy; iv) more than half of the counties cannot achieve full efficiency, caused by input redundancy and output deficiency. A novelty of this article is to present an overall picture of detailed zoning strategies for high-quality development and indicate some potential misjudgments and mismanagement caused by the lack of consideration of natural conditions. However, even though the potential spatial clustered pattern of sustainability is revealed in our case, more evidence is needed to examine the presence of systematic spatial variation. Highlights: Considering the heterogeneity of natural conditions, a parametric slacks-based measure of efficiency (SBM) is employed. Conventional SBM would overestimate(underestimate) the efficiency under the interference of natural conditions. The adjusted overall efficiency evaluates the performance on sustainable development of local governments more accurately. The trade-off between economy and environment helps to identify the function zones.